Rare sugars in soils: insights on their presence, persistence, and potential for carbon sequestration - Lemas, Stephanie, author; Boot, Claudia M., advisor; Conant, Richard, committee member; von Fischer, Joe, committee member; Levinger, Nancy E., committee member (Colorado State University. Libraries, 2024)
Carbon (C) is a fundamental element in the biosphere, cycling through all its natural pools. However, due to human activity, the flux of C into the atmosphere has accelerated, impacting the climate in significant and consequential ways. Awareness of this has prompted world-wide research into different mitigation strategies, including both reducing the flux of C into the atmosphere and active carbon dioxide removal (CDR) from the atmosphere. Soil represents a substantial C reservoir with the capacity to store large amounts of C. Our research focuses on the role of chiral molecules, specifically rare sugars, to enhance the storage of C in soil. To assess the feasibility of this idea, we designed an experiment to test whether soil microorganisms were able to consume and respire 14 rare sugars. We found that some rare sugars showed very little or repressed respiration, but that most showed moderate or high respiration rates. This finding prompted the hypothesis that soil microorganisms have evolved the capacity to grow on rare sugars because those rare sugars are present in the soil. To test this, we designed another experiment to check for the presence of rare sugars, specifically rare hexoses, in soils. Hexose sugars are among the most important small molecules in nature, in part because they are essential sources of energy for most cells. D-glucose, the most abundant hexose, is well-known due to its roles in both cellular respiration and photosynthesis; however, D-glucose is far from the only hexose in nature. Plants and microorganisms produce not only D-glucose, but also D-fructose, D-galactose, and D-mannose, and they contribute these hexoses to soils in different proportions. These four hexoses are considered common in soil and have been incredibly well-studied, but they represent only a small fraction of the hexoses possible in soil systems. In this study, we used gas chromatography-mass spectrometry (GC-MS) to measure hexoses in diverse soils crowdsourced from across the contiguous United States. In addition to the four common hexoses, we identified a fifth hexose: a rare ketohexose corresponding to the overlapping retention times of psicose and tagatose ("PsiTag"). This rare ketohexose, or possible mixture of these two rare ketohexoses, was present in every soil we sampled. To the best of our knowledge, this is the first time a rare ketohexose has been identified in a soil extract. The ubiquitous presence of a rare hexose in soils shifts the paradigm and challenges the narrative about which hexoses are truly common. These two experiments explore the potential of rare sugars for soil C sequestration via bio-transformative CDR (BtCDR) by examining their presence and the persistence in soils. As a result of our investigation, we determined that each rare sugar falls into one of two categories: having high turnover in soil, and therefore low C sequestration potential, or having high recalcitrance in soil and high C sequestration potential. Experimental data suggest that PsiTag and L-fructose have high recalcitrance in soil, but that L-glucose has high turnover in soil. Further research is needed to verify these findings and explore additional rare sugars. Although preliminary data indicate that rare sugar monosaccharides would not serve as effective long-term C sinks in soil, we believe that rare sugars may have a yet unknown role to play in soil C dynamics. This thesis sheds new light into the previously uninvestigated presence of rare sugars in soil, their implications for sustainable C storage, and their potential contributions to a holistic approach to climate change mitigation.
Keywords: gas chromatography-mass spectrometry; rare sugar; soil chemistry; hexose; carbon dioxide removal; soil carbon